A good family - Goldman, Matt, 1962- (Forge, Tor Publishing Group, 2023)
"Katie Kuhlmann's marriage is falling apart. But she has a secure job, her children are healthy, and her house, a new construction in the prestigious Country Club neighborhood of Edina, Minnesota, is beautiful. She can almost ignore the way her husband, Jack, has been acting--constantly checking his phone, not going to work, disappearing from the house only to show up again without explanation. Tension in the Kuhlmann house only gets worse when Adam "Bagman" Ross, a mutual friend from college, happens to be in the neighborhood and in need of a place to stay. Jack is quick to welcome him into the sanctity of their home, but Jack's strange behavior only gets worse, and Katie fears their new guest is also harboring a dark secret. As she begins to uncover the truth, she realizes that something is terribly wrong--and she must race to protect her family as danger closes in"--